PERAN MODERASI EXTERNAL HUMAN RESOURCE PARTNERSHIP PADA HUBUNGAN STRATEGI PEREKRUTAN DAN PENGEMBANGAN KOMPETENSI DALAM MENINGKATKAN KINERJA SDM PADA KLINIK KESEHATAN SWASTA DI KOTA MEDAN - Vinna Pratiwi Agustyn; Tomy Sun Siagian; Dhea Agusty Ningrum (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Private healthcare clinics face increasingly complex challenges in human resource management due to intensified competition for competent healthcare professionals, high workforce mobility, and evolving competency requirements driven by digital transformation in the healthcare sector. These conditions require organizations not only to implement effective recruitment strategies and competency development programs but also to establish strategic partnerships with external institutions to enhance human resource performance. This study aims to examine the effects of recruitment strategy and competency development on human resource performance, as well as to investigate the moderating role of external human resource partnership in private healthcare clinics in Medan City, Indonesia. A quantitative research approach was employed using a survey method involving 95 respondents, consisting of clinic managers, physicians, and nurses selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), including assessments of the measurement model, structural model, and hypothesis testing. The findings reveal that both recruitment strategy and competency development have positive effects on human resource performance. Furthermore, external human resource partnership strengthens the relationships between recruitment strategy and human resource performance, as well as between competency development and human resource performance, indicating that external partnerships serve as a strategic mechanism for enhancing the effectiveness of human resource management practices. This study contributes to the advancement of Strategic Human Resource Management by positioning external human resource partnership as a collaborative capability that reinforces the implementation of recruitment strategies and competency development initiatives to improve human resource performance in private healthcare clinics.. Keywords: Recruitment Strategy, Competency Development, External Human Resource Partnership, Human Resource Performance.   Abstrak: Klinik kesehatan swasta menghadapi tantangan yang semakin kompleks dalam pengelolaan sumber daya manusia akibat meningkatnya persaingan memperoleh tenaga kesehatan yang kompeten, tingginya mobilitas tenaga profesional, serta perubahan kompetensi yang dipengaruhi oleh transformasi digital pada sektor pelayanan kesehatan. Kondisi tersebut menuntut organisasi tidak hanya menerapkan strategi perekrutan dan pengembangan kompetensi yang efektif, tetapi juga membangun kemitraan strategis dengan berbagai institusi eksternal untuk meningkatkan kinerja sumber daya manusia. Penelitian ini bertujuan menganalisis pengaruh recruitment strategy dan competency development terhadap human resource performance, serta menguji peran moderasi external human resource partnership pada klinik kesehatan swasta di Kota Medan. Penelitian menggunakan pendekatan kuantitatif dengan metode survei dan melibatkan 95 responden yang terdiri atas kepala klinik, dokter, dan perawat yang dipilih menggunakan teknik purposive sampling. Analisis data dilakukan menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS) melalui pengujian model pengukuran, model struktural, dan pengujian hipotesis. Hasil penelitian menunjukkan bahwa recruitment strategy dan competency development berpengaruh positif terhadap human resource performance. External human resource partnership memperkuat hubungan antara recruitment strategy dan competency development dengan human resource performance, sehingga kemitraan eksternal berperan sebagai mekanisme strategis dalam meningkatkan efektivitas praktik pengelolaan sumber daya manusia. Penelitian ini memberikan kontribusi terhadap pengembangan Strategic Human Resource Management dengan menempatkan external human resource partnership sebagai kapabilitas kolaboratif yang memperkuat implementasi strategi perekrutan dan pengembangan kompetensi dalam meningkatkan human resource performance pada klinik kesehatan swasta. Kata kunci: Strategi Recruitment, Pengembangan Kompetensi, Kolaborasi Eksternal, Kinerja